The normality of political administration and state violence: casuistry, law, and drones - Rothe, Dawn (Critical criminology, 2014)
Large unmanned aerial vehicles (i.e., drones) equipped with missiles and bombs or battle-equipped have progressively become the newest wave in "warfare." We argue that the use of drones for targeted assassinations is merely a new technological tool for state violence that is increasingly becoming a regular exercise of the US power in the construction and reification of the broader social geopolitical order. Further, it is through law, domestic and international, that state violence, wars and the use of drones for targeted assassinations are legitimated and are a normality, and continuation of, the political management of the state. Taken with the core of humanitarian law that legitimates war and state violence, we suggest that the use of drones can be interpreted within the body of legislation, political discourse, and laws that serve to normalize and legitimize their use: no different than such processes that occurred with the technological advances that offered military tanks, aerial bombing, projectile missiles or even nuclear and chemical weapons.